‘Solving the problem of reality’ in Virginia Woolf’s Flush - Pauline Macadré (Cahiers Victoriens et Edouardiens)
Flush’s main character, Elizabeth Barrett Browning’s spaniel, can be seen as the epitome of Victorianism, an embodiment of its tradition of anthropomorphism and a displaced portrait of his mistress, but it is also the pretext for a modernist reconstruction of Victorian society, towards a new literary (re)presentation of the sensorial world. No longer neglected by critics and scholars, Flush has been widely analysed as encapsulating the social issues of the mid-nineteenth century in terms of class and gender, adopting the point of view of a dog to expose the confinement and submission women had to face—in the Victorian period, but also in Woolf’s own time. The Edwardian perspective allows Woolf to use Flush as the conveyor of modernity—not merely because writing the biography of a dog questions the established societal and literary codes, but also because the de-familiarization of the world through animal eyes aims at ‘solving the problem of reality’. The reader becomes the witness of a reconfiguration of perception as primeval instincts are inscribed within Flush’s body, smell takes over eyesight and the novel depicts a world distorted by synaesthesia. Despite the human qualities Flush is endowed with, a reversal still occurs which highlights the human beings’ otherness and reduces their/our language to hieroglyphic, undecipherable signs, unable to grasp reality. The animal’s perspective ushers in a tentative description of ‘the world seen without a self’, a world that escapes the screen of the human eye/I and where the unobserved and uncanny nature of things can be unveiled.